Answer:
![(4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6b0j5aa9l6dr1dcukz4brasf0qfe4c7u4y.png)
Explanation:
let the original fraction be
( with denominator 1 more than numerator )
Subtracting 3 from numerator/ denominator gives
=
![(n-3)/(n-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/jelsdr4jx6jflq2vbbkg7ugja3mizpzfkl.png)
Given that the fraction is now equivalent to
, then
=
( cross- multiply )
2(n - 3) = n - 2, distribute left side
2n - 6 = n - 2 ( subtract n from both sides )
n - 6 = - 2 ( add 6 to both sides )
n = 4
and n + 1 = 4 + 1 = 5
Thus original fraction is
![(4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6b0j5aa9l6dr1dcukz4brasf0qfe4c7u4y.png)